Reaching conceptual stability by re-articulating empirical and theoretical work on affordances - Malo, Roman; Prié, Yannick (Frontiers in Psychology, 2024)
Theoretical developments on affordances have proliferated, resulting in a lack of conceptual stability and a potential compromise in scientific validity. However, affordances should not be discarded, given their centrality in post-cognitive theories and their widespread reuse across various research domains. Empirical research on affordances remains sparse, out of sync with theoretical advancements, and thus unable to contribute effectively to scientific progress due to its disarticulation with theoretical work. That is why re-articulating theoretical and empirical investigations on affordances is needed to pave a more fruitful path for the concept’s advancement. To accomplish this objective, emphasis must be placed on empirical research, leveraging recent theoretical propositions and devising corresponding empirical methodologies. The proposed requirements and framework represent a step in this endeavor.